Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia dan Thailand - Fidanti Pramay Sheilla; Nazaruddin Malik (Program Studi Ekonomi Pembangunan, 2020)
This study discusses export growth and the importance of economic growth in Indonesia and Thailand from 1979 - 2018. The method used is multiple linear regression analysis to see the effect of the independent variables on the variables used. The results of this study show the facts in the f-statistics test of Indonesian exports do not have a significant influence with the direction of a negative relationship to economic growth. This concerns the significance of raw materials produced from export products not entirely from within the country and the supported products are still primary products. While imports in Indonesia, exports and imports in Thailand have a significant influence on economic growth.